The Role of Innovation Capability and Social Media Marketing Capability to Improve SME’s Social Media Performance: English - Sabandar, Michelle Clysia (Sekolah Tinggi Manajemen IPMI, 2025)
Many Florists in Indonesia use Social. This quantitative research uses a purposive sampling technique that analyses 98 respondents who were collected using an online questionnaire. The theory used is Resource-Based Theory (RBT), where an analysis technique using SMART-PLS. Social Media Marketing Communication Capability, Social Media Product Development, and Innovation Capability are the variables studied to determine whether they will produce Social Media Performance for SME's Florist in Java. The results showed that Innovation Capability did not produce Social Media Performance with a t-value of 0.618 and a p-value of 0.537. Furthermore, social Media Marketing Communication Capability can also not produce Social Media Performance with a t-value of 1.085 and a p-value of 0.278. Meanwhile, Social Media Product Development Capability has a big role in producing Social Media Performance. Of the three variables, only Social Media Product Development has a significant role in producing Social Media Performance.